2001
DOI: 10.1103/physrevlett.87.017005
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Density of States inMgB2

Abstract: We report inelastic neutron scattering measurements of the phonon density of states in Mg 11B2, which has a superconducting transition at 39.2 K. The acoustic phonons extend in energy to 36 meV, and there are highly dispersive optic branches peaking at 54, 78, 89, and 97 meV. A simple Born-von Kàrmàn model reproduces the mode energies, and provides an estimate of the electron-phonon coupling of lambda approximately 0.9. Furthermore, the estimated boron and magnesium contributions to the isotope effect are in q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
127
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 14 publications
28
127
1
Order By: Relevance
“…λ is seen to increase correspondingly from 0.8 to 0.9. The extracted values of λ and θ D for pristine MgB 2 are in agreement with earlier estimates of these quantities from the specific heat experiments 26 , similar resistivity measurements 27 , phonon DOS measurements 28 and calculations 29 . DISCUSSION It can be seen from Fig.4, that the T c decreases with carbon fraction upto x=0.3, beyond which it shows no significant change.…”
Section: Methodssupporting
confidence: 79%
“…λ is seen to increase correspondingly from 0.8 to 0.9. The extracted values of λ and θ D for pristine MgB 2 are in agreement with earlier estimates of these quantities from the specific heat experiments 26 , similar resistivity measurements 27 , phonon DOS measurements 28 and calculations 29 . DISCUSSION It can be seen from Fig.4, that the T c decreases with carbon fraction upto x=0.3, beyond which it shows no significant change.…”
Section: Methodssupporting
confidence: 79%
“…Replacing 10 B with 11 B results in a sizeable isotope shift [3] to lower temperatures which points to BCS superconductivity. Other experiments, such as heat capacity [4,5], photoemission spectroscopy [6], and inelastic neutron scattering [7,8] also support the picture that MgB 2 is a phonon-mediated superconductor in the weak-to-moderate coupling regime.High pressure studies traditionally play an important role in superconductivity. A large magnitude of the pressure derivative dT c /dP is a good indication that higher values of T c may be obtained through chemical means.…”
mentioning
confidence: 73%
“…We now repeat the same calculation with the McMillan equation for MgB 2 using the logarithmically averaged phonon energy from inelastic neutron studies [7] [33]. Inserting these values into Eq.…”
mentioning
confidence: 99%
“…The observation of a boron isotope effect has lead to MgB 2 being described as a phonon-mediated BCS superconductor [4] although the observed T c is at, or above, the early theoretical predictions based on phonon-mediated coupling within the BCS theory [6]. It has recently been shown that the T c can be as large as that observed within the moderate to strong phonon-mediated BCS theory due to the large density of states at the Fermi level and high phonon frequencies [7][8][9]. However, it has been suggested that the predicted crossing of the Fermi surface by the boron σ and π bands at different regions of the Brillouin zone can have a significant impact on superconductivity in MgB 2 [10,11].…”
Section: Introductionmentioning
confidence: 99%